The Effect of Dysmenorrhea Exercise on Reducing Primary Menstrual Pain (Dysmenorrhea) in Adolescent Girls at SMPN 3 Pabuaran, Subang Regency, Indonesia - Cici Susanti; Puput Sri Mulyani (HM Publisher, 2023)
Dysmenorrhea exercise is a type of exercise or physical exercise specifically designed to help reduce the symptoms of dysmenorrhea or severe menstrual pain. Dysmenorrhea is a common condition in most women and can cause pain, lower abdominal cramps, nausea, vomiting, and other discomfort during the menstrual period. This study aimed to determine the effect of dysmenorrhea exercise on reducing primary menstrual pain (dysmenorrhea) in adolescent girls at SMPN 3 Pabuaran, Subang Regency, Indonesia. This study is experimental research with a pre-post-test approach. This study uses primary data obtained from direct observation of respondents. A total of 30 research subjects participated in this study, where the research subjects met the inclusion criteria. The inclusion criteria for the study were women of childbearing age with complaints of dysmenorrhoea at SMPN 3 Pabuaran, Subang Regency, Indonesia, who were willing to participate in this study. This study shows that dysmenorrhea exercise intervention is effective in reducing pain intensity in dysmenorrhea sufferers. There was a decrease in pain intensity after dysmenorrhea exercise and it was stated to be statistically different, p<0.05. In conclusion, there is an effect of dysmenorrhea exercises on reducing primary dysmenorrhea pain in adolescent girls at SMPN 3 Pabuaran, Subang Regency, Indonesia.